Issues in the Management of Acute Agitation: How Much Current Guidelines Consider Safety? - Pacciardi, Bruno; Mauri, Mauro; Cargioli, Claudio; Belli, Simone; Cutugno, Biagio; Di Paolo, Luca; Pini, Stefano (Frontiers in Psychiatry, 2013)
Agitated behavior constitutes up to 10% of emergency psychiatric interventions. Pharmacological tranquilization is often used as a valid treatment for agitation but a strong evidence base does not underpin it. Available literature shows different recommendations, supported by research data, theoretical considerations or clinical experience. Rapid tranquilization is mainly based on parenteral drug treatment and the few existing guidelines on this topic, when suggesting the use of first generation antipsychotics and benzodiazepines, include drugs with questionable tolerability profile such as chlorpromazine, haloperidol, midazolam and lorazepam. In order to systematically evaluate safety concerns related to the adoption of such guidelines, we reviewed them independently from principal diagnosis while examining tolerability data for suggested treatments. There is a growing evidence about safety profile of second generation antipsychotics for rapid tranquilization but further controlled studies providing definitive data in this area are urgently needed.